Primary Prevention of Breast Cancer - Mulawan Umar (Arkus, 2016)
Breast cancer is the most common cancer among women and with high mortality rate. There is evidence showing the influence of life style and environmental factors on the development of mammary gland cancer (high-fat diet, alcohol consumption, and lack of physical exercise). Primary prevention may contribute to a decrease in morbidity and mortality. The aim of this paper is to review current knowledge and reports regarding primary prevention of breast cancer.